2021
DOI: 10.3389/fpsyg.2021.653258
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Input Factors in Second Language Acquisition of the English Article Construction

Abstract: Based on the Competition Model, the current study investigated how cue availability and cue reliability as two important input factors influenced second language (L2) learners' cue learning of the English article construction. Written corpus data of university-level Chinese-L1 learners of English were sampled for a comparison of English majors and non-English majors who demonstrated two levels of L2 competence in English article usage. The path model analysis in structural equation modeling was utilized to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In sum, case marking was one of the most reliable cues in native speakers' speech, and this was mirrored in learners' speech, matching the first scenario in Section The Current Study. While this study was not designed to demonstrate the direct relationship between input properties and production or to demonstrate the actual learning process, the results corroborate Zhao and Fan (2021), who showed using statistical modeling that the cue reliability in the input was a reliable predictor of L2 learning.…”
Section: Cue Ranking In Each Groupsupporting
confidence: 75%
See 4 more Smart Citations
“…In sum, case marking was one of the most reliable cues in native speakers' speech, and this was mirrored in learners' speech, matching the first scenario in Section The Current Study. While this study was not designed to demonstrate the direct relationship between input properties and production or to demonstrate the actual learning process, the results corroborate Zhao and Fan (2021), who showed using statistical modeling that the cue reliability in the input was a reliable predictor of L2 learning.…”
Section: Cue Ranking In Each Groupsupporting
confidence: 75%
“…Second, by analyzing spontaneous production by learners, the study demonstrates how learners themselves use the cues of word order, case marking, and animacy to express transitive relations, extending the prior work within the framework of the competition model that has focused on comprehension. As far as I know, the recent study by Zhao and Fan (2021) was the first to investigate both the input and production in L2 learning (they used written production data while the current study used oral production data), and as they suggested, "[l]anguage production is perhaps the area that has the most urgent need for more empirical data" (p. 4).…”
Section: The Current Studymentioning
confidence: 99%
See 3 more Smart Citations